Is Resting State Functional MRI Effective Connectivity in Movement Disorders Helpful? A Focused Review Across Lifespan and Disease - Sussman, Bethany L.; Wyckoff, Sarah N.; Heim, Jennifer; Wilfong, Angus A.; Adelson, P. David; Kruer, Michael C.; Gonzalez, Maria Jose; Boerwinkle, Varina L. (Frontiers in Neurology, 2022)
In the evolving modern era of neuromodulation for movement disorders in adults and children, much progress has been made recently characterizing the human motor network (MN) with potentially important treatment implications. Herein is a focused review of relevant resting state fMRI functional and effective connectivity of the human motor network across the lifespan in health and disease. The goal is to examine how the transition from functional connectivity to dynamic effective connectivity may be especially informative of network-targeted movement disorder therapies, with hopeful implications for children.